2008
DOI: 10.3181/0801-rm-19
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Atopic Dermatitis-Like Skin Lesions by DA-9102, a Natural Medicine Isolated from Actinidia arguta, in the Mg-Deficiency Induced Dermatitis Model of Hairless Rats

Abstract: DA-9102 isolated from Actinidia arguta is a candidate of natural medicine currently under Phase II clinical trial for atopic dermatitis in Korea. In this study, spontaneous dermatitis was induced by magnesium deficiency in hairless rats and this system was applied to assess the suppressive effects of DA-9102 on atopic dermatitis-like skin disease. Oral administration of DA-9102 at a dose of 100 mg/kg for 16 days substantially suppressed the occurrence of spontaneous dermatitis. Eczematous skin lesions, water l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Importantly, TRPV3 appears to be under the negative control of Mg 2+ and it was postulated that dietary Mg 2+ deficiency may liberate TRPV3 from this tonic inhibitory control, leading to a constitutively active TRPV3 channel . Indeed, a Mg 2+ -deficient diet causes dermatitis and scratching behavior in rats (Choi et al, 2008). Taken together, these findings imply a therapeutic potential for topically applied TRPV3 antagonists in the management of pruritus secondary to (atopic) dermatitis.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 68%
“…Importantly, TRPV3 appears to be under the negative control of Mg 2+ and it was postulated that dietary Mg 2+ deficiency may liberate TRPV3 from this tonic inhibitory control, leading to a constitutively active TRPV3 channel . Indeed, a Mg 2+ -deficient diet causes dermatitis and scratching behavior in rats (Choi et al, 2008). Taken together, these findings imply a therapeutic potential for topically applied TRPV3 antagonists in the management of pruritus secondary to (atopic) dermatitis.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 68%
“…84 In an animal model, Actinidia arguta improved dermatitis skin lesions in magnesium-deficient hairless rats by decreasing infiltration of the skin by inflammatory cells and preventing histopathological remodeling of the dermis and epidermis while preventing transepidermal water loss. 85 Saururus chinensis, described by the same group, 86 demonstrated similar anti-inflammatory effects to A arguta, resulting in decreased hypertrophy and hyperkeratosis of the dermis and epidermis and decreased itching behavior in the atopic subjects. In addition, they demonstrated a shift toward the T H 1 cell pathway with no effect demonstrated on T H 2.…”
Section: Asthmamentioning
confidence: 92%
“…The reports have shown that the natural immune modulator system derived from the fruit extract has a therapeutic effect on atopic dermatitis Kim, Lee, Son, & Kim, 2009;Park et al, 2005Park et al, , 2007. The extract obtained from dried A. aruguta, named DA-9102, was a natural medicine candidate to control atopic dermatitis in Korea (Choi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%